PENGARUH KEMAMPUAN SOFTSKILL KARYAWAN TERHADAP KEPUASAN MAHASISWA DIBIDANG PELAYANAN DITINJAU DARI SISI GENDER PADA FAKULTAS EKONOMI UNIVERSITAS DHARMA ANDALAS PADANG - Yusnaena, Syahrul Effendy Syahril (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
This research will discuss about the Effects of Employee Softskill Ability initiative,Commitment, Creativity, Communication, Integration and Discipline Against StudentSatisfaction in ministry in terms of the gender At the Faculty of Economics, University ofAndalas Padang Dharma, data from this study by using a cross sectional survey. Theanalytical tool used is multiple linear regression models. The study population was all thestudents of the Department of Management FEB Unidha Padang were female. active in theacademic year 2015/2016 running and samples were taken as many as 100 people usingRandom Sampling technique Acidental with research initiatives variable, variablecommunication, integrity, discipline variable positive and significant impact to thesatisfaction of temporary variables and variable commitment Creativity, no effectsignificantly to the Student Satisfaction UNIDHAKeywords: Ability soft skills, gender, student satisfaction